Komunikasi kebangsaan berbasis budaya Bali di sekolah multikultural - Dewi Rachmawati (Universitas Garut, 2026)
Abstract The era of globalization encourages increasingly intensive exchange of culture, information, and values between countries. This is interesting in the Balinese context because the existence of international schools coexists with strong local cultural values. Balinese culture, which is based on the philosophy of social and spiritual harmony, is an important foundation in building a community life that upholds balance and togetherness, so that schools can function as spaces for cross-cultural communication between local and international communities. Departing from this context, this study aims to understand how Balinese cultural values are integrated into national communication practices in a multicultural school environment. This study uses a qualitative approach with a case study method at one international school in Bali. Data were collected through in-depth interviews, observation, and documentation, then analyzed thematically using the Social Identity Theory framework and multicultural education theory as an analytical framework. Data analysis was carried out thematically by conducting data reduction, data presentation, drawing conclusions, and verification. The results of the study indicate that national communication in multicultural schools occurs through the process of integrating Balinese cultural values into educational activities. Local values have been proven to function as a reinforcement of national identity and a bridge of harmony between local and international communities in the educational environment in Bali. This research is important to examine how education plays a role as a means of forming national identity in an increasingly diverse global society, and how local wisdom can become the foundation for sustainable national character and education. Keywords: National communication; Balinese culture; multiculturalism; international school. Abstrak Era globalisasi mendorong pertukaran budaya, informasi, dan nilai-nilai yang semakin intensif antarnegara. Hal ini menjadi menarik dalam konteks Bali karena keberadaan sekolah internasional berdampingan dengan kuatnya nilai-nilai budaya lokal. Budaya Bali yang berlandaskan filosofi harmoni sosial dan spiritual menjadi fondasi penting dalam membangun kehidupan masyarakat yang menjunjung tinggi keseimbangan dan kebersamaan, sehingga sekolah dapat berfungsi sebagai ruang komunikasi lintas budaya antara komunitas lokal dan internasional. Berangkat dari konteks tersebut, penelitian ini bertujuan untuk memahami bagaimana nilai-nilai budaya Bali diintegrasikan dalam praktik komunikasi kebangsaan di lingkungan sekolah multikultural. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus pada salah satu sekolah internasional di Bali. Data dikumpulkan melalui wawancara mendalam, observasi, dan dokumentasi, kemudian dianalisis secara tematik dengan menggunakan kerangka Social Identity Theory serta teori pendidikan multikultural sebagai kerangka analisis. Analisis data dilakukan secara tematik dengan melakukan reduksi data, penyajian data, penarikan kesimpulan dan verifikasi. Hasil penelitian menunjukkan bahwa komunikasi nasional di sekolah multikultural terjadi melalui proses pengintegrasian nilai-nilai budaya Bali ke dalam kegiatan pendidikan. Nilai-nilai lokal telah terbukti berfungsi sebagai penguat identitas nasional dan jembatan harmoni antara masyarakat lokal dan masyarakat internasional dalam lingkungan pendidikan di Bali. Penelitian ini penting untuk mengkaji bagaimana pendidikan berperan sebagai sarana pembentukan identitas nasional dalam masyarakat global yang semakin beragam, dan bagaimana kearifan lokal dapat menjadi landasan bagi karakter dan pendidikan nasional yang berkelanjutan. Kata-kata kunci: Komunikasi nasional; budaya Bali; multikulturalisme; sekolah internasional.